2002
DOI: 10.1007/s004140100249
|View full text |Cite
|
Sign up to set email alerts
|

Detection of cardiomyocyte apoptosis in forensic autopsy cases

Abstract: The purpose of the present study was to determine reliable parameters for the detection of apoptotic cells for use as a diagnostic marker during the early stage of acute myocardial infarction (AMI) in forensic autopsy cases. Myocardial tissues taken from forensic autopsy cases were examined by immunohistochemical and molecular-biological methods using the terminal deoxynucleotidyl transferase-mediated dUTP biotin nick end-labelling (TUNEL) and the DNA laddering methods. In cases of AMI with a time period betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 11 publications
0
17
0
Order By: Relevance
“…Previous studies have reported the presence of apoptosis in most cases of AMI [34][35][36][37]. These studies demonstrated that during an AMI widespread apoptosis occurs and is evident only a few hours after the onset of AMI, prior to the appearance of necrosis [35].…”
Section: Discussionmentioning
confidence: 94%
“…Previous studies have reported the presence of apoptosis in most cases of AMI [34][35][36][37]. These studies demonstrated that during an AMI widespread apoptosis occurs and is evident only a few hours after the onset of AMI, prior to the appearance of necrosis [35].…”
Section: Discussionmentioning
confidence: 94%
“…Another issue is that 5 of 22 of the published studies did not report the time from the onset of symptoms to death. Most autopsies were performed within 24 to 30 hours of patient death because excessively long time periods would have limited the accurate detection of apoptosis [21]. Unfortunately, in half of the studies, the time from the death to autopsy is uncertain.…”
Section: Resultsmentioning
confidence: 99%
“…The presence of TUNEL staining in nuclei of myocardial cells is a function of the time from death to autopsy because postmortem autolysis damages the DNA and limits detection of the characteristic apoptosis. Nakatome et al reported that all 6 cases with autopsies between 5 to 30 hours after death showed TUNEL-positive cells in the infarct while none of 6 cases who had autopsies 24 to 63 after death showed TUNELpositive cells [21].…”
Section: Histologic Evidence Of Dna Damage Consistent Withmentioning
confidence: 99%
See 2 more Smart Citations